Assistance in Silage Making to Increase Community Capacity in Providing Forage During the Dry Season for Ruminant Livestock - Umbu A Hamakonda; David Januarius Djawapatty; Victoria Ayu Puspita; Ferdinandus Bai; Anggela Marici Bupu (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The continuous availability of forage throughout the year, both in quality and quantity, is an absolute requirement for livestock development. Forage that is abundant during the rainy season must be processed by preserving it so that the nutritional quality of the forage remains guaranteed. One technology for processing feed using preservation techniques is making silage. Making silage is done to preserve and minimize nutrient loss and can also improve feed nutrition. The main problem faced by goat farming groups in West Lengkosambi Village, Riung District, Ngada Regency, is the provision of quality and continuous feed. To increase breeders' knowledge about making goat feed using the silage process, it is necessary to provide training to breeders in Lengkosambi Barat Village, Riung District, Ngada Regency. This training activity was carried out on 11-12 October 2024. 57 participants attended the silage-making training. Participants' enthusiasm was very high when taking part in the silage-making training. Participants have the willingness to play an active role in making silage. This activity concludes that the training carried out was able to increase the knowledge and skills of members of the West Lengkosambi Village goat farming group regarding the benefits and techniques for making silage and its use as goat feed. Providing quality feed during the dry season can be overcome so that livestock growth and production levels will be achieved optimally.